Systematic Literature Review: Sistem Manajemen Kelembagaan Efektif pada Pusat Kegiatan Belajar Masyarakat (PKBM) di Indonesia - Rochman, Abdur; Rasyad, Achmad; Wahyuni, Sri; Dayati, Umi; Ellyn Sugeng Desyanty (STAI Terpadu Yogyakarta, 2024)
This research is a review of effective institutional management at the Community Learning Activity Center (PKBM). The research method used is reviewing reputable scientific articles found on Google Scholar. The data collection technique in the research was carried out by collecting various relevant articles. The findings in the study provide an explanation of the importance of institutional management in PKBM in order to realize quality education. Governance management in PKBM institutions can be carried out using the principles of planning, organizing, implementing, monitoring and evaluating. This principle is an effective step in increasing effectiveness which is based on quality standardization and institutional academic quality. On the other hand, in order to recruit human resources, an appropriate plan is needed as a concrete form of a quality institution. Recruitment of human resources can be done using a staffing strategy by paying attention to the career stages of tutors and employees, as well as their dismissal. The success of the PKBM institution as a community social institution has become a pattern that is accompanied by standardization of the educational curriculum which is relevant to government regulations.